Lessons from good language teachers - Griffiths, Carol 1945-; Tajeddin, Zia 1962- (Cambridge University Press, 2020)
What makes a good language teacher? This up-to-date, practical book addresses that question from a 'human' perspective, recognising that teachers are not just machines, but have feelings, needs and identities of their own. As the twenty-two topics of the chapters in this volume clearly indicate, language teachers are complex individuals, who are expected to have a range of personal qualities, to be able to satisfy the needs of their students and to have the knowledge and skills to provide instruction in a range of language areas. Not only that, but all of these requirements are constantly changing. The authors present new insights from the real teaching environment that will be an invaluable help to language teachers at all stages of professional development
Keywords: Teacher effectiveness; Effective teaching; Language and languages -- Study and teaching; Languages, Modern -- Study and teaching; Lernerfolg; Sprachunterricht; Aufsatzsammlung